Three-Dimensional Morphology and Connectivity of Organic Pores in Shale from the Wufeng and Longmaxi Formations at the Southeast Sichuan Basin in China. (17th May 2021) - Jiang, Tao; Jin, Zhijun; Hu, Zongquan; Du, Wei; Liu, Zhongbao; Zhao, Jianhua
Abstract : Organic pores play an important role in shale reservoirs. Organic pores occur where shale gas was produced and accumulated. However, there is little scientific understanding of the distribution and connectivity of organic pores. Organic pore types and their structural characteristics were studied using a total organic carbon (TOC), thin section, focused ion beam scanning electron microscope (FIB-SEM), and nano-CT. The samples were from the Wufeng Formation in the Upper Ordovician and Longmaxi Formations from the lower Silurian. The results show that organic matter is mainly concentrated in the Wufeng Formation and the bottom of the Longmaxi Formation and that the middle and upper parts of the Longmaxi Formation contain a low amount of organic matter. The shale of the Wufeng-Longmaxi Formation has high maturity, and its organic pores are well developed. There are three types of organic pores: algae, graptolite, and pyrobitumen pores. The pore connectivity of shale with a high organic content is better than that of shale with a low organic content. The volume of the organic pores accounts for more than 50% of the volume of the organic matter. Majority of the organic pores have an aperture smaller than 100 nm and are round, nearly circular, and elliptical in morphology. Most of the organic pores in a shale formation are developed in pyrobitumen, and most of the larger organic pores are concentrated at the center of solid pyrobitumen. The organic pores in pyrobitumen have the best connectivity and are the most favorable reservoir spaces and migration channels for shale gas, which is a crucial point of reference for future research of shale gas.